Acute Abdomen in Fertile Women with Pain Located in the Right Iliac Fossa. Appendicitis? Observational Study - Arredondo, Guillermo Padron (Archives of Clinical and Medical Case Reports, 2017)
Background: Gynecological disorders related to general surgery may be considered in five themes: 1) Acute abdomen. 2) Unexpected and gynecological disorders discovered during exploratory laparotomy. 3) Pain during pregnancy. 4) Pregnancy and urinary disorders and 5) cancer of gynecological cause. Being the first two disorders which more often a general surgeon faces. Material and Methods: In order to determine the incidence of gynecological disorders attended for generasurgeons, and iterative appendectomies resulting in cases of acute abdomen in fertile women was conducted a retrospective, observational cohort analysis over a period of 4 years in a secondary hospital under newly created with exploratory laparotomy and clinical symptoms of acute abdomen and / or probable acute appendicitis. Results: During the study period were surgically intervened 126 women of childbearing age in our country (between 11 and 45 years of age) with acute abdomen and probable acute appendicitis of which 19 met the criteria for admission to study due to gynecoobstetric disease without acute appendicitis. There was only one case of morbidity (textiloma) and no mortality. Discussion: In our work we found an incidence of 15% for acute appendicitis diagnostic fails which is below international standards and is known generally from 6 to 25% of operations for acute appendicitis they reveal a normal appendix and this number rises to 30 to 40% in the case of women of childbearing.